P204 Phenotypic and treatment characteristics of IBD patients with pseudopolyps in the era of biological treatments. Endoscopic characteristics of pseudopolyps are associated with the use of biological treatment: A multi-centre retrospective study. (16th January 2018) - Politis, D S; Katsanos, K H; Papamichael, K; Choukour, M; Tua, J; Skamnelos, A; Theopistos, V; Kavvadias, A; Balomenos, D; Baltayiannis, G; Tzabouras, N; Tsianos, E V; et al.
Abstract: Background: Pseudopolyps are encountered during endoscopy in patients with IBD. 1 Aim of the study was to examine the treatment of patients with IBD and pseudopolyps, with special interest in biological agents, with description of patients' phenotypic characteristics alongside with endoscopic characteristics of pseudopolyps. Methods: Retrospective study of medical charts and endoscopic records of patients with IBD and pseudopolyps, with report of pseudopolyps at least at one endoscopy for each patient, diagnosed and followed up from 1/1/2000 till 1/7/2017 at University hospital of Ioannina, University Hospital of Nancy and Mater Dei Hospital. Exclusion criteria were incomplete follow-up. Recording of the medical therapy used for remission during follow-up, alongside with demographics of patients and extent of IBD was performed. Recording of pseudopolyps' characteristics such as size, number of pseudopolyps and time interval of presentation of pseudopolyps from diagnosis was performed and statistical analysis about correlation of pseudopolyps' characteristics and the use of biological agents was carried out. Results: Seventy-nine patients with IBD and pseudopolyps were included at the study, Forty-five patients (56.7%) with UC and Thirty-four patients (43.3%) with CD. The demographic and phenotypic characteristics of patients are presented in Table 1. Twenty-nine patients (36.7%) from the total of the Seventy-nine patients received biological agent based treatment at the end of follow-up. Treatment characteristics of patients are presented in Table 2. The size of pseudopolyps above 1.5 cm ( p < 0.001) and the number of pseudopolyps above 10 ( p = 0.012) in endoscopy, were associated with biological agent based treatment but not their presence before 12 months from diagnosis ( p = 0.419), Table 3. Conclusions: Patients with pseudopolyps face a high burden of IBD in terms of increased immunosuppression treatment. Endoscopic characteristics of pseudopolyps such as size above 1.5 cm and number above 10 can be associated with need for biological treatment suggesting that pseudopolyps may have a place in endoscopic scores. Reference: 1. Politis DS, Katsanos KH, Tsianos EV, et al. Pseudopolyps in inflammatory bowel diseases: Have we learned enough? World J Gastroenterol, 2017;23:1541–51.